Antimicrobial susceptibility profiles and genotyping of Neisseria meningitidis of serogroup C, Italy, 2000–2020 - Vacca, Paola; Fazio, Cecilia; Neri, Arianna; Ambrosio, Luigina; Carannante, Anna; Lista, Florigio; Fillo, Silvia; Ciammaruconi, Andrea; Fortunato, Antonella; Stefanelli, Paola (Frontiers in Microbiology, 2024)
Background In Italy the introduction of meningococcal C conjugate vaccine in 2005 has led to a significant reduction of invasive meningococcal disease (IMD) caused by Neisseria meningitidis of serogroup C (MenC). However, this serogroup is still responsible of sporadic cases, clusters and local outbreaks. The study aims to investigate the genotype and antimicrobial susceptibility profile of MenC isolates collected in Italy from 2000 to 2020. Methods Bacterial isolates and biological samples (blood or cerebrospinal fluid) from invasive meningococcal cases are collected and characterized at the National Reference Laboratory for IMD of Istituto Superiore di Sanità. Antimicrobial susceptibility was determined by MIC Test Strip Method and interpreted according to the EUCAST breakpoints guideline. Genotypic characteristics, including multi locus sequence typing (MLST), finetype, and antimicrobial resistance target genes were performed and analyzed using the PubMLST database. Genomic comparison of core genome MLST (cgMLST) of MenC genomes was also carried out. Results From 2000 to 2020, a total of 665 MenC isolates were investigated for antimicrobial susceptibility and 301 for genotyping. Over two decades, almost all MenC isolates resulted susceptible to antimicrobials with few isolates resulting resistant to ciprofloxacin (N = 2), penicillin G (N = 13), and rifampicin (N = 9), respectively. Molecular typing of MenC obtained from isolates or clinical specimens identified mostly the genotype C:P1.5-1,10-8:F3-6:ST-11(cc11). However, phylogenetic analysis, performed on genomes from MenC isolates, identified two sub lineages, 11.1 and 11.2, among cc11, of which the sub lineage 11.2 was the predominant. Conclusion Wider application of the genomic analysis and monitoring of antimicrobial susceptibility represent key aspects of IMD surveillance and to monitor the continued evolution of these hyperinvasive strains.